Team-Oriented Leadership and Auditors' Willingness to Raise Audit Issues - Nelson, Mark W.; Proell, Chad A.; Randel, Amy E. (The Accounting Review, 2016)
ABSTRACT This paper reports five studies examining audit team members' willingness to raise audit issues. The first study is a survey of interacting audit teams that provides evidence that team members are more willing to speak up when they view their leader as team-oriented (i.e., emphasizing team success as opposed to the leader's own personal advancement). Experiments 1–3 provide converging evidence that audit seniors are more willing to speak up to a team-oriented leader and about issues that are aligned with that leader's concerns. Experiment 4 provides evidence that the effect of team-oriented leadership on willingness to speak up is mediated by team members' commitment to the team leader and, to a lesser extent, by their identification with their team, but not by concerns about the immediate or eventual repercussions of speaking up. Together, these studies provide evidence that auditors' willingness to raise audit issues is affected by what the auditor has to say and how they think their message will be received, potentially affecting audit effectiveness and audit efficiency. Data Availability: Contact the authors.